Wife's Consent as a Valid Condition for Reconciliation: A Juridical Study of Articles 164 and 165 of the Compilation of Islamic Law - L, Yusri; Aris, Ismail; Fadila, Anisa Sri; Putri, Melani; Maharani, Erzy Aurelia (Faculty of Sharia and Islamic Law Institut Agama Islam Negeri Bone, 2025)
This research discusses the issue of a wife's consent as a valid requirement for reconciliation (a legal study on Articles 164 and 165 of the Compilation of Islamic Law). It aims to determine the rights of a wife in reconciliation based on the Compilation of Islamic Law and the Islamic legal perspective on the position of a wife's consent rights in reconciliation as a valid requirement for reconciliation. To gather data on this issue, library research was conducted. The data obtained were analyzed using inductive, deductive, and comparative methods. Furthermore, a juridical-normative and juridical-theological approach was used in analyzing the data. In Islamic law, the authority to reconcile is an absolute right of the husband during the iddah period. Meanwhile, the Compilation of Islamic Law implicitly states that the consent and approval of the wife are valid requirements for reconciliation; in other words, it may be declared invalid by a ruling from the Religious Court. The text regarding the wife's rights in reconciliation, as outlined in the Compilation of Islamic Law, has a contextual meaning that enables the wife to access administrative benefits, guarantees, and legal protection from the state. Because the state only serves and recognizes the event of reconciliation if there is an authentic document in the form of a Marriage Certificate Extract. It does not annul the lawful reconciliation according to Islamic law. On the contrary, the existence of principles in Islamic law actually emphasizes the need to achieve public welfare and to reject or prevent anything that has the potential to cause harm.